Transmission loss analysis in an infinite tube with multiple discontinuities - (:unkn) unknown (My University, 2023)
Abstract: The effect of perforated screens and absorbing linings on the sound propagation is investigated using Mode Matching technique. This method is applied for the prediction of transmission loss (dB) for different parameter values of the geometry. Both low and high porosity are considered for perforated screens. In order to show the effect of the tube radius, length of the partial lined part and perforated screen porosities on the propagation phenomenon, graphics are plotted. The results demonstrate the significance of the parameters of the problem in the predictions for transmission loss (dB).
Keywords: Fizik; Elektromanyetizma, Akustik, Isı Transferi, Klasik Mekanik ve Akışkanlar Dinamiği; Akustik; Temel Bilimler; Physics; Electromagnetism, Acoustics, Heat Transfer, Classical Mechanics and Fluid Dynamics; Acoustics; Natural Sciences; Temel Bilimler (SCI); AKUSTİK; Natural Sciences (SCI); PHYSICS; ACOUSTICS; Akustik ve Ultrasonik; Fizik Bilimleri; Acoustics and Ultrasonics; Physical Sciences; infinite tube; mode matching; perforated screen; transmission loss; transmission loss; infinite tube; perforated screen; mode matching